Cysteine‐Rich Peptides: Hyperstable Scaffolds for Protein Engineering. (17th November 2020) - González‐Castro, Rafael; Gómez‐Lim, Miguel A.; Plisson, Fabien
Abstract: Cysteine‐rich peptides (CRPs) are small proteins of less than 100 amino acids in length characterized by the presence of disulfide bridges and common end‐to‐end macrocyclization. These properties confer hyperstability against high temperatures, salt concentration, serum presence, and protease degradation to CRPs. Moreover, their intercysteine domains (loops) are susceptible to residue hypervariability. CRPs have been successfully applied as stable scaffolds for molecular grafting, a protein engineering process in which cysteine‐rich structures provide higher thermodynamic and metabolic stability to an epitope and acquire new biological function(s). This review describes the successes and limitations of seven cysteine‐rich scaffolds, their bioactive epitopes, and the resulting grafted peptides. Abstract : Better in the loop : Cysteine‐rich peptides possess hyperstability against high temperatures, salt concentration, serum presence, and proteolytic degradation. These peptides have been successfully used as stable scaffolds for molecular grafting, a protein engineering process in which cysteine‐rich structures enclave an exogenous and bioactive epitope that provides higher thermodynamic and metabolic stability to the epitope and new functionality to the scaffold.